Association between bevacizumab with cancer drug therapies and drug-induced interstitial lung disease in patients with solid tumor: A systematic review and meta-analysis of randomized clinical trials. (June 2022) - Nozawa, Kazuki; Takatsuka, Daiki; Endo, Yuka; Horisawa, Nanae; Ozaki, Yuri; Kataoka, Ayumi; Kotani, Haruru; Yoshimura, Akiyo; Hattori, Masaya; Sawaki, Masataka; Iwata, Hiroji
Abstract: Purpose: This study aimed to determine interstitial lung disease (ILD) incidences in patients receiving cancer drug therapies with or without bevacizumab treatment. Methods: Systematic searches of PubMed, Embase, and Cochrane Library were conducted in January 2021. The main inclusion criteria were randomized clinical trials that compared bevacizumab with standard treatment in patients with solid tumors. Cochrane Collaboration's Tool was used for assessing risk-of-bias. Results: Thirteen records involving 7201 patients were included in the meta-analysis. There were 42 ILD events in bevacizumab groups and 72 in control groups. In bevacizumab groups, the odds ratio for ILD was 0.62 (95% CI 0.42–0.92; p = 0.02), which was a significantly lower incidence than the control. This tendency was shown in targeted therapy groups but not in the cytotoxic agent groups. Conclusion: Our data suggest that bevacizumab may reduce the incidence of ILD. Highlights: Interstitial lung disease is currently one of the significant challenges. There is limited guidance on the management of interstitial lung disease. Adding bevacizumab is well known for enhancing the antitumor effect. Anti-VEGF antibody protected against vascular-to alveolar leakage of protein. Antiangiogenic inhibitors may reduce the risk of interstitial lung disease.